Distant Agricultural Landscapes - Jennifer Clapp (Sustainability Science, 2015)
This paper examines the relationship between the development of the dominant industrial food system and its associated global economic drivers and the environmental sustainability of agricultural landscapes. It makes the case that the growth of the global industrial food system has encouraged increasingly complex forms of “distance” that separate food both geographically and mentally from the landscapes on which it was produced. This separation between food and its originating landscape poses challenges for the ability of more localized agricultural sustainability initiatives to address some of the broader problems in the global food system. In particular, distance enables certain powerful actors to externalize ecological and social costs, which in turn makes it difficult to link specific global actors to particular biophysical and social impacts felt on local agricultural landscapes. Feedback mechanisms that normally would provide pressure for improved agricultural sustainability are weak because there is a lack of clarity regarding responsibility for outcomes. The paper provides a brief illustration of these dynamics with a closer look at increased financialization in the food system. It shows that new forms of distancing are encouraged by the growing significance of financial markets in global agrifood value chains. This dynamic has a substantial impact on food system outcomes and ultimately complicates efforts to scale up small-scale local agricultural models that are more sustainable.